The use of the PCT index in railway motion sickness incidence evaluation. (May 2015) - Braccesi, Claudio; Cianetti, Filippo; Scaletta, Renzo
The aim of this paper is to define an evaluation method to quantify the index of motion sickness incidence (MSI) in railway motion conditions. This index is widely used in the literature to quantify illness symptoms that occur as a result of generic low-frequency motions (kinetosis). In fact, only one standard exists (ISO 2631) and it was defined for general motion and in particular for vertical acceleration motion conditions. No standards have been written that consider the conditions experienced in railway motion. This paper reports an evaluation approach that can be used to examine illness symptoms experienced during rail trips and involves indices and methods well-known in the rail industry. In particular the proposed approach involves the P ct index (EN 12299: Comfort index on curve transition) and some weighting curves for the filtering of accelerometer signals that are also specified in railway regulations (EN 12299, ISO 2631). The proposed method, that is consistent with a theoretical model that has been reported in the literature, allows the MSI index to be obtained as a function of travel time and/or track distance. The model is validated through a comparison with experimental data available in literature and with experimental data recorded for a tilting train during tests performed in Slovenia.